2018
DOI: 10.1016/j.diamond.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of (111)-faced single-crystal diamond plates by laser nucleated cleaving

Abstract: Single-crystal diamond plates with surfaces oriented in a (111) crystal plane are required for high-performance solid-state device platforms ranging from power electronics to quantum information processing architectures. However, producing plates with this orientation has proven challenging. In this paper, we demonstrate a method for reliably and precisely fabricating (111)-faced plates from commercially available, chemical-vapor-deposition-grown, type-IIa single-crystal diamond substrates with (100) faces. Ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…To confirm the (111) membrane orientation, X-ray diffraction (XRD) and electron backscattered diffraction Figure 1D shows an XRD spectrum of the original bulk single crystal diamond with a pronounced peak at 2θ = 44 , confirming the (111) orientation of the crystal. 21 Figure 1E shows an EBSD map recorded from the overgrown membrane, confirming further that it is single crystal (111)-oriented diamond through analysis of kikuchi pattern information derived from back scattering of electrons in SEM.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…To confirm the (111) membrane orientation, X-ray diffraction (XRD) and electron backscattered diffraction Figure 1D shows an XRD spectrum of the original bulk single crystal diamond with a pronounced peak at 2θ = 44 , confirming the (111) orientation of the crystal. 21 Figure 1E shows an EBSD map recorded from the overgrown membrane, confirming further that it is single crystal (111)-oriented diamond through analysis of kikuchi pattern information derived from back scattering of electrons in SEM.…”
supporting
confidence: 59%
“…19 However, despite the remarkable progress in nanofabrication of diamond cavities, 8,20 all photonic resonators to date were fabricated from (100)-oriented diamond, primarily because this is the most common orientation provided by commercial suppliers and the difficulty in engineering and polishing (111)-oriented crystals. 21 This, however, limits the potential coupling strength of many color centers to cavities, since most centers studied to date have dipoles oriented along the <111> direction, and the dipole overlap with the cavity field is therefore not optimal in cavities fabricated from (100)-oriented diamond. Conversely, in (111)-oriented diamond, the overlap is optimal, and superior Purcell enhancement is expected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using a 100x, NA = 0.9 air objective, Jamali et al [ 48 ] showed that proper alignment of the dipole and optical axes results in a increase in collected photons, corresponding to an SNR increase of ≈1.3. Although the production of (111)-faced diamonds is traditionally a laborious and expensive process, recent developments of laser-nucleated-cleaving techniques [ 49 ] provide an attractive alternative. In this technique, a series of laser pulses is used to nucleate and propagate cleaves along desired (111) planes within a standard (100)-faced diamond, resulting in large, flat, (111)-faced plates even without any polishing.…”
Section: Maximizing Photon Collection Efficiencymentioning
confidence: 99%
“…Furthermore, different surface orientations may allow for access to different chemical terminations; for example chemical groups that are sterically prohibited on the (100) surface may be permitted on (111) surfaces [86]. Such surfaces are difficult to prepare because polishing is more challenging for these orientations, but recent work has shown that near-atomically smooth surfaces are possible with cleaving [87].…”
Section: Surfacesmentioning
confidence: 99%